The state and prospects of development of the mineral resource base of solid minerals of the Bolivarian Republic of Venezuela - Aslambek A. Germakhanov; Alexander I. Chernykh; Mikhail M. Girfanov; Valery A. Istomin; Andrey S. Svatkov (Руды и металлы)
The status and prospects of the mineral resource base of solid minerals of the Bolivarian Republic of Venezuela, as well as possibilities for developing the Russian-Venezuelan cooperation in the field of geology and mineral resource management are considered. Venezuela has world's largest oil reserves and a wide range of solid minerals (gold, diamonds, nickel, bauxite, iron ores, tantalum and niobium, other rare and base metals, various industrial minerals), which resource base retains significant growth prospects. The main direction of intensification of the mining industry is associated with implementation of a large-scale Governmental program for the geological study and development of the Orinoco Mining Belt in the northern Bolivar State. Within the belt, a number of commercial mineral deposits and much significant potential resources of the solid minerals have been identified and localized, requiring a modern reassessment in order to increase their investment attractiveness for major foreign mining companies. A prominent place in the development of the mineral resource complex of Venezuela can be occupied by Russian mining companies in cooperation with organizations of the Russian Geological Survey.